Educational gap between high school students and el alto public university - Quispe Condori, Yelmo (2024)
The objective of the research was to determine the educational gap between secondary education and higher education students in their curricular, economic, technological and social factors in Municipal District 14 of El Alto, giving relevance to the task that the teaching staff has of training high school students. Upright and capable of facing university challenges. The methodology used was a quantitative  and documentary study  where a survey was applied  to 100 students equally divided into groups of 25 participants in the areas of: Health Science, Engineering, Productive Technological Development, Economic, Financial and Administrative Sciences, and Social  Sciences of the Public University of El Alto. The results showed a significant educational gap of 90%, which concludes with the need to implement training  programs for teachers and students to improve educational quality  and increase their chances of entering university.